DHX9 interacts with APOBEC3B and attenuates the anti-HBV effect of APOBEC3B. Issue 1 (1st January 2020) - Chen, Yanmeng; Shen, Bocun; Zheng, Xiaochuan; Long, Quanxin; Xia, Jie; Huang, Yao; Cai, Xuefei; Wang, Deqiang; Chen, Juan; Tang, Ni; Huang, Ailong; Hu, Yuan
ABSTRACT: Hepatitis B virus (HBV) is a partially double-stranded DNA virus that replicates by reverse transcription. We previously demonstrated that the host restriction factor-APOBEC3B (A3B) inhibited HBV replication which was dependent on its deaminase activity during reverse transcription. However, the host factors involved in the process of regulating the anti-HBV function of A3B are less known. In this research, to obtain a comprehensive understanding of the interaction networks of A3B, we conducted coimmunoprecipitation and mass spectrometry to identify A3B-interacting proteins in the presence of HBV. By this approach, we determined that DExD/H-box helicase 9 (DHX9) suppressed the anti-HBV effect of A3B, and this suppression was dependent on their interaction. Although DHX9 did not affect the deamination activity of A3B in vitro assay or the viral DNA editing of A3B in HepG2-NTCP cells that support HBV infection, it inhibited the binding of A3B with pgRNA. These data suggest that DHX9 can interact with A3B and attenuate the anti-HBV efficacy of A3B. Abbreviations: 3D-PCR: differential DNA denaturation PCR; APOBEC3: apolipoprotein B mRNA-editing catalytic polypeptide 3; cccDNA: covalently closed circular DNA; co-IP: coimmunoprecipitation; DDX: DExD-box RNA helicases; HBc: HBV core protein; HBV: hepatitis B virus; HepAD38: HepG2 cell line stably transfected with HBV DNA; HepG2-NTCP: HepG2 cell line stably transfected with Na+/taurocholate cotransporter polypeptide; Huh7: human hepatoma cell line; pgRNA: pregenomic RNA; PPI: protein–protein interactions; RC DNA: relaxed circular DNA.